PERAN PENTING MANAJEMEN DATA DALAM MENINGKATKAN KUALITAS LAYANAN PERBANKAN DIGITAL - Dira Finanta; Muhammad Irwan Padli Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Customers can now obtain quick and easy financial services from anywhere at any time thanks to the invention of digital banking services. Customers may find it simpler to execute tasks related to opening account books, banking transactions, registering, communicating, and canceling accounts when they use digital banking services. In this sense, client performance will regrettably suffer as a result of the caliber of digital banking services. The purpose of this study is to determine how national security is impacted by the deterioration of digital banking. The goal of digital-based services is to satisfy client needs by delivering information using digital technology and a keyboard or mouse. Digital services can be accessed anywhere, at any time. Because of this, there is less direct communication between